Implementación de manufactura esbelta en la línea de producción de la empresa SEDEMI S.C.C. - Carpio Mejía, Juan Carlos (2012)
The present work it’s about the optimization of time in the process through the use of one of the tools of improvement of the Philosophy of Lean Manufacturing. Supporting this, inside the are of supplying-production in SEDEMI S.C.C. Company, where it is set up to resort to this methodology to decrease time in production during the process of manufacturing of miscellaneous. To carry out the system of lean Manufacturing in the field of production as principal goal established, it should be apply based on several types of research such as: applied, field and descriptive. The implementation of this system is no just decrease time but to get advantages in flexibility and cost price once it be finished.